ENHANCING MUSICAL INTELLIGENCE USING AMKA APP IN FOURTH GRADE OF SD SUPRIYADI 02 SEMARANG - Priyanto, Wawan; Mustadi, Ali; Haryanto, Haryanto (Prodi PGMI FTK UIN Ar-Raniry Banda Aceh, 2024)
Some problems faced by elementary school teachers in developing their students' musical intelligence included teachers lacking knowledge and skills in music, teachers not optimally utilizing technology in music learning, and there are rarely technology-based learning media for music learning. This study aims to determine the effectiveness of using the AMKA App to improve the musical intelligence of 4th-grade students of SD Supriyadi 02 Semarang. This study is quantitative research using One Group Pre-test Post-test Design. The subjects in this study were 29 4th-grade students of SD Supriyadi 02 Semarang. The post-test results showed that three students belonged to the musical category, 14 students belonged to the Quiet musical category, and 12 students belonged to the less musical category. The N-Gain test results also showed that four students showed no improvement in musical intelligence, 20 students showed improvement in the low category, five students showed improvement in the medium category, and there were no students who entered the effectiveness improvement in the high category. These results prove that the AMKA App as learning media is effective in increasing the musical intelligence of grade 4 students of SD Supriyadi 02 Semarang.Keywords: Musical intelligence, teaching media, music